BUDAYA SADRANAN DALAM DUNIA DIGITAL : SEBUAH UPAYA CULTURAL PROMOTION MELALUI SOSIAL MEDIA INSTAGRAM - ADI SABDONO,; WISNU SANJAYA, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
Nyadran is a tradition of cleaning tombs by Javanese people, generally in rural areas. In Javanese, Nyadran comes from the word sadran which means ruwah syakban. Nyadran is a series of cultures in the form of cleaning the ancestral graves, sowing flowers, and the climax of the festive festivities at the ancestral graves.The COVID-19 pandemic in Indonesia is part of the ongoing coronavirus disease (COVID-19) pandemic around the world. The disease is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The first positive cases of COVID-19 in Indonesia were detected on March 2, 2020. Until now, the Indonesian government is still working to fight the virus. In the current pandemic situation, Sadranan's customary activities have undergone many changes, even though this custom had wanted to be eliminated in 2020 since the beginning of the Covid-19 pandemic. Sadranan culture is still carried out but still prioritizes health protocols.